Flex5Gware: Flexible and efficient hardware and software platforms for 5G network elements and devices. Issue 9 (19th July 2016) - Payaró, Miquel; Färber, Michael; Vlacheas, Panagiotis; Bartzoudis, Nikolaos; Tillman, Fredrik; Ferling, Dieter; Berg, Vincent; Rautio, Tapio; Serrano, Pablo; Sabella, Dario
Abstract: This paper presents the Flex5Gware project, whose goal is to deliver highly reconfigurable hardware (HW) platforms and HW‐agnostic software (SW) platforms for 5G network elements and terminal devices. Flex5Gware will enable 5G HW/SW platforms to meet the requirements imposed by the growth in mobile traffic and the diversity of applications by increasing their capacity, reducing their energy footprint and enhancing their scalability and modularity. To put in place this vision in this early stage of 5G PPP research, Flex5Gware is designing and prototyping key building blocks of 5G HW/SW platforms. In particular, the developed technologies will be evaluated and demonstrated with proofs‐of‐concept by the end of the project. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The figure represents the Flex5Gware concept. The four technology groups studied in the project are depicted as horizontal planes. In each of these groups, there are key building blocks, which are represented by the square boxes (coloured boxes represent multiple HW technologies and grey boxes represent HW‐agnosticism). The dashed ovals represent Flex5Gware PoCs, either stand‐alone (the oval includes only one box) or integrated (the oval contains more than one box).